Skeletal Anchorage as a Therapeutic Alternative for Mandibular Second Molar Impaction: A Prospective Case-Control Study - Martina Mezio; Federica Altieri; Michele Cassetta (MDPI AG, 2024)
Background: The treatment of mandibular second molar (MM2) impaction presents a challenge for orthodontists and requires a surgical-orthodontic approach. This study aims to compare the effectiveness of two techniques for treating impacted MM2: a traditional technique using brass wire and a technique employing skeletal anchorage. Methods: Twelve MM2 with mesio-angular impaction, with an inclination angle between 25° and 40° and an impaction depth between 4 and 10 mm, were selected and randomly divided into two treatment groups. Patients in Group A were treated using the traditional brass wire technique, while those in Group B underwent treatment with a skeletal anchoring technique that utilized a miniscrew positioned in the retromolar region and an elastic sling chain. For both groups, treatment time and the influence of the disimpaction technique on oral health-related quality of life (OHRQoL) were evaluated using the short-form Oral Health Impact Profile (OHIP-14). Results: The results indicated an average treatment time of 168.67 ± 52.32 days for Group A and 76 ± 10.17 days for Group B, with a statistically significant difference (p-value = 0.0002). Regarding the impact on the patients' OHRQoL, Student's t-test did not reveal a statistically significant difference between the two groups at 3 and 7 days of follow-up. Conclusions: Both techniques are considered effective for the treatment of impacted MM2 (angulation 25-40°, depth 4-10 mm). The use of skeletal anchorage significantly reduces treatment times without negatively affecting OHRQoL. The results of this study should be confirmed by further studies with larger sample sizes.